Le classi medie: definizione, mobilità e declino nel caso italiano - Bison, Ivano (SocietàMutamentoPolitica, 2013)
In this contribution three different Istat dataset on Families and Social Subjects (1998, 2003 and 2009) are analyzed in order to assess the evolution of middle class. The article also tries to understand how change in productive system transformed the way in which ascribed and acquisitive factors shape life trajectories of individuals and their effects in redefining the structure of stratification in Italian society as a whole.